Dr. Norwahida developes RAMOS, a user-friendly system to manage work stress - Nur Hartini, Mohd Hatta (UMPSA, 2023)
PEKAN, 27 October 2023 - As an industry practitioner facing challenges in analysing risks associated with psychosocial hazards, Dr. Norwahida Yakub, a 35-year-old lecturer from the Faculty of Industrial Sciences and Technology (FSTI) at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), has developed the Risk Assessment Matrix of Occupational Stress (RAMOS), a more time-efficient and user-friendly tool.